Theater, document, archive - Risso Nieva, José María (Universidad Nacional del Litoral, 2021)
The theater, as an object of study, is a complex and difficult phenomenon to study. These considerations are part of a necessary problematization of the methodology associated with the work of scenic reconstruction and documentary collection. The discussion related to the formulations about the archive by Jacques Derrida with contemporary theater theory and our studies on dramaturgy. We focus on the process of search, exhumation, and junction developed in the analysis of dramaturgical practices articulated around the cycle «Teatro Libre» (Tucumán, 1985). We want to understand how research contributes to shaping an archive to come.